2018
DOI: 10.1590/1806-9061-2016-0445
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Fatty Acid Profiles of Ducks Fed a Diet Supplemented with Aronia (Aronia Melanocarpa) Powder

Abstract: The present study evaluated the effects of aronia powder on growth performance and fatty acid profiles of ducks. A total of 90 ducks (oneday-old pekin, 48 males and 42 females) were distributed according to a completely randomized design into two treatments (control and 1% aronia powder) with 3 replicates of 15 birds per pen for 42 d. Apart from the feed:gain ratio, the other growth performance parameters, including initial body weight, final body weight, weight gain, and feed intake, did not differ significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Hussain et al (2017) reported that chickens fed a diet containing 3% mealworm meals, showed increase in weight gain and dressing percentage, including feed cost and economic profit. In terms of using chokeberry, Lee et al (2018) used the level of 1% chokeberry powder in the diet of ducks and found improvement in the weight gain and the feed:gain ratio. However, no study has so far evaluated the impact of a pelleting combination of TM powder and CBP meal on the growth performance of Pekin ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Hussain et al (2017) reported that chickens fed a diet containing 3% mealworm meals, showed increase in weight gain and dressing percentage, including feed cost and economic profit. In terms of using chokeberry, Lee et al (2018) used the level of 1% chokeberry powder in the diet of ducks and found improvement in the weight gain and the feed:gain ratio. However, no study has so far evaluated the impact of a pelleting combination of TM powder and CBP meal on the growth performance of Pekin ducks.…”
Section: Discussionmentioning
confidence: 99%